Enhancing broadly neutralising antibody suppression of HIV by immune modulation and vaccination - Nel, Carla; Frater, John (Frontiers in Immunology, 2024)
Although HIV infection can be managed with antiretroviral drugs, there is no cure and therapy has to be taken for life. Recent successes in animal models with HIV-specific broadly neutralising antibodies (bNAbs) have led to long-term virological remission and even possible cures in some cases. This has resulted in substantial investment in human studies to explore bNAbs as a curative intervention for HIV infection. Emerging data are encouraging, but suggest that combinations of bNAbs with other immunomodulatory agents may be needed to induce and sustain long-term viral control. As a result, a number of clinical trials are currently underway exploring these combinations. If successful, the impact for the millions of people living with HIV could be substantial. Here, we review the background to the use of bNAbs in the search for an HIV cure and how different adjunctive agents might be used together to enhance their efficacy.